Transportation and revolt : pigeons, mules, canals, and the vanishing geographies of subversive mobility - Shell, Jacob, 1983- (Mobility studies, 2015)
"Modes of transportation understood, by political regimes in different times and places, as intrinsically useful for clandestine movement, subversive mobility, and smuggling for revolt. Contents: Chapters look at canal transportation, several types of animal transportation (mules, elephants, camels and sled-dogs are all treated at some length), and inner-city freight-carrying infrastructure"--Provided by publisher.